The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1208/s12249-012-9868-2
|View full text |Cite
|
Sign up to set email alerts
|

Solid Dispersion of Ursolic Acid in Gelucire 50/13: a Strategy to Enhance Drug Release and Trypanocidal Activity

Abstract: Solid dispersions (SDs) are an approach to increasing the water solubility and bioavailability of lipophilic drugs such as ursolic acid (UA), a triterpenoid with trypanocidal activity. In this work, Gelucire 50/13, a surfactant compound with permeability-enhancing properties, and silicon dioxide, a drying adjuvant, were employed to produce SDs with UA. SDs and physical mixtures (PMs) in different drug/carrier ratios were characterized and compared using differential scanning calorimetry, hot stage microscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 35 publications
(50 reference statements)
3
27
0
Order By: Relevance
“…FTIR analysis is a useful tool to investigate intermolecular interactions, through shift or broadening of the bands in the spectra [42,43]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR analysis is a useful tool to investigate intermolecular interactions, through shift or broadening of the bands in the spectra [42,43]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that RAP bands in the liposomes were more broadened, appearing at a higher temperature, suggesting that RAP was at least partially converted from the crystalline to the amorphous state in liposomes. An important consequence is that amorphous drugs are more soluble and thus could present enhanced bioavailability [43]. In some spectra in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the different ratio of SA and Gelucire were optimized to obtain maximum entrapment, and drug loading with sustained release (SI Table 2). It is evident from the ratio of SA and gelucire (SI Table 2) that addition of gelucire led to an increased release of drug from nanoparticles as gelucire is [33] known for faster dissolution. When SLNs prepared with gelucire, release was estimated faster since in 16.8 hr more than 90 % drug was released, whereas slower release with SLNs prepared with SA was observed i.e.…”
Section: Fabrication Of Mtx Loaded Solid Lipid Nanoparticles(slns-mtx)mentioning
confidence: 99%
“…SLNs-MTX was prepared using hot homogenization technique (Scheme 1) [33,34]. The high velocity stirring was employed to acquire a pre-emulsion phase.…”
Section: Fabrication Of Mtx Loaded Solid Lipid Nanoparticles(slns-mtx)mentioning
confidence: 99%
“…Thus, efforts have been made to develop UA derivatives with more favorable PK properties 34 . In addition, several studies have attempted to improve bioavailability by modifying the formulation of UA 4, 35, 36 . Nevertheless, we found that phase II anti-oxidant genes could still be slightly induced in leukocytes following an oral dose of 100 mg/kg UA (Figure 7).…”
Section: Discussionmentioning
confidence: 99%